(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
This paper seeks to elucidate the status of the Koryo Saram in Kazakhstan in relation to South Korean diplomacy. After a historical overview of the Koryo Saram in Kazakhstan, the authors analyze the cultural and geopolitical role of the Koryo Saram in Kazakhstan-South Korea relations. The authors review existing literature and provide their insights from an outside perspective written firstly in English. The authors conclude that the Koryo Saram are in a precarious position as a diaspora, and risk losing their unique heritage barring intentional protection efforts on the part of the states of Kazakhstan and South Korea. The authors draw a distinction between protection and preservation efforts, favoring the former for its promotion of authenticity in cultural revival and agency for the diasporic group. This paper is the first to provide prescriptive policy analysis of diaspora diplomacy and the Koryo Saram, building off of economical, legal, and anthropological historiography. Key words: Koryo Saram, diaspora diplomacy, soviet koreans.